OPTIMALISASI PEMBERDAYAAN PELAKU USAHA TENUN CAG-CAG MELALUI EDUKASI LITERASI KEUANGAN - Komang Krishna Yogantara; Putu Agus Prayogi; I Putu Agus Suarsana Ariesta; Sulistyoadi Jokosaharjo; Gunawan Wibisono; Made Hedy Wartana; I Nengah Aristana (Synergy and Society Service, 2023)
The economic growth of a region will indirectly affect the increase or decrease in the number of poverty in that region. One of the factors that can reduce poverty is to encourage and develop the real sector, but there are still many woven fabric craftsmen in Tangkup Village who do not fully understand how to manage a business that is being started, especially in terms of good financial management. The purpose of this community service is to help business actors in woven cloth craftsmen in Tangkup Village to fully understand how to manage a business that is being started, especially in terms of good financial management. Through Thematic Field Work Lectures by conducting educational activities and financial management assistance for woven fabric craftsmen in Tangkup Village which was carried out proven to be effective in order to increase adequate understanding of good and correct bookkeeping (accounting).